Physiological Responses, Performance, Behaviour, and Welfare of Garut Sheep Cared using Semi-Intensive System in Indonesia - Yasin Pradana Maulana; D Ramdani; H Indrijani; U Yunasaf; N Mayasari (Jurnal Ilmu Ternak dan Veteriner, 2022)
Sheep farming in Indonesia still relies on the intensive system which is very labor-intensive, movement restrictions, and reduced quantity of sheep can be kept, developed countries, on the other hand, have evolved a semi-intensive system that may minimize the number of staff while still providing welfare to the sheep. This study aimed to compare the performance, physiological responses, behavior, and welfare of reared Garut sheep in semi-intensive management with outdoor pen and full indoor pen treatments, employing a T-test experimental design using ten replicates (n=10). This experiment used 20 ewes sheep (one-year-old) with an average body weight of 18.74±2.53 kg. This experiment found no difference in dry matter intake (gram/head/day) or average daily gain (gram/head/day) between both treatments (P0.05). When compared to ewes with full indoor pen, ewes with access to outdoor pen had better physiological status especially heart rate and respiratory rate, particularly in the morning and afternoon (P0.05). The ratio of blood N/L for ewes with an outdoor pen showed better results (P0.05), and the rearing environment also did not show any difference nor induce stress on livestock with access to outdoor pen (P0.05). Ewes' welfare increases and they become more active after being provided access to outdoor pen. In conclusion, a semi-intensive system with an outside enclosure enhances Garut ewes' performance while also improving their physiological health and welfare index fulfillment. This approach has to be promoted throughout Indonesia for better farming management.